Evaluation of the Antibacterial Activity of Cucurbita maxima Seed Oil Against Multidrug-Resistant Foodborne Pathogens - Esra Elmaghbub,; Halima Nashnush,; Rabya Lahmer, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study aimed to investigate the antibacterial activity of cold-pressed pumpkin seed oil (Cucurbita maxima) against selected foodborne multidrug-resistant (MDR) pathogens. The oil's inhibitory effect was evaluated against Klebsiella pneumoina, Salmonella enterica, Bacillus cereus, and Staphylococcus aureus using the agar well diffusion method. Seven concentrations (5%-100%) were tested with amoxicillin as the positive control and dimethyl sulphoxide (DMSO) 5% as the negative control. The results demonstrated that pumpkin seed oil exhibited a concentration-dependent antibacterial activity. Significant inhibition was observed even at low concentrations (5%), with significant differences between the different concentrations (p<0.05). These findings suggest that Cucurbita maxima seed oil promises to be a natural antibacterial agent and could serve as an alternative for managing MDR foodborne infections.